Chinese Government Enterprise Driven Strategies in Rural Poverty Alleviation : A Case Study of China's Rural Area of Henan - Min, Song; Regina Garai, Abdullah (International Journal of Religion (IJOR), 2024)
The implementation of China’s targeted poverty alleviation strategy has not only promoted changes in China’s poverty alleviation methods but also influenced corporate poverty alleviation activities. It is crucial for enterprises to improve the efficiency of poverty alleviation and integrate with targeted poverty alleviation work to complete corporate poverty alleviation activities and achieve effective results. This study aims to explore the effectiveness of corporate poverty alleviation in rural poor areas under the background of targeted poverty alleviation in China. Based on this, Shangshui County in Henan Province, China, was selected as the research object. Using a combination of qualitative and quantitative research methods, an evaluation model of corporate poverty alleviation effectiveness was established through the Analytic Hierarchy Process (AHP) based on survey data to assess the effectiveness of corporate poverty alleviation. The results show that poverty alleviation enterprises in this county have played a significant role in the development of poor areas during the poverty alleviation process, but there is still room for improvement.